Structural funds and regional economic growth: The Greek experience - Adamantia Kechagia; Foteini Kyriazi (Review of Economic Analysis (REA), 2021)
The impact of structural funds of the European Union (EU) on regional economic growth is a matter of both political and economic importance. The large and regular payments made across the EU to countries and regions within them were and are meant to promote various aspects of growth and development and to encourage structural changes that foster investments and economic reforms. But how much of these aims have they been achieved? In this paper we provide considerable empirical evidence that Greek regions have, for the most part, benefited by the various disbursements of EU structural funds. We shed partial light on where this funding went to and to how it potentially contributed to Greek growth but we also raise a number of questions about the viability of the current productive structure of the Greek economy and its over-reliance on tourism. Our results provide support on the efficacy of the payments but leave open the problem of where these payments should be allocated, the monitoring of their absorption and the end impact in the economic cycle within a country.
Keywords: 61; H40; O43; R11; R58; 330; economic growth; European Union; Greece; regional development; production structure; structural funds